Global journal of medical pharmaceutical and biomedical update - Agnihotri, Arun Kumar, 1970-; Aruoma, Okezie I., 1951- (Scientific Scholar LLC, 2020)
An open-access peer-reviewed journal committed to publishing high-quality articles in the field of Biomedicine, Surgery and Pharmacology.